The Positive Influence of Polyphenols Extracted From Pueraria lobata Root on the Gut Microbiota and Its Antioxidant Capability - Xu, Xiao; Guo, Ying; Chen, Shaoqin; Ma, Wenliang; Xu, Xinlei; Hu, Shuning; Jin, Lifang; Sun, Jianqiu; Mao, Jian; Shen, Chi (Frontiers in Nutrition, 2022)
Pueraria lobata, an edible food and medicinal plant, is a rich source of bioactive components. In this study, a polyphenol-rich extract was isolated from P. lobata. Puerarin was identified, and the high antioxidant bioactivity of the P. lobata extract was evaluated using the methods of 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2′-azinobis-(3-ethylbenzthiazoline-6-sulphonate) (ABTS), and hydroxyl free radical scavenging ratio. Additionally, the IC50 values of DPPH, ABTS, and hydroxyl radical scavenging activities were 50.8, 13.9, and 100.4 μg/ml, respectively. Then, the P. lobata extract was administered to C57Bl/6J mice and confirmed to have a superior effect on enhancing the antioxidant status including improving superoxide dismutase activity, glutathione peroxidase peroxide activity, total antioxidant capacity activity, and malondialdehyde contents in vivo. Furthermore, the P. lobata extract had beneficial and prebiotic effects on the composition and structure of gut microbiota. Results showed that the P. lobata extract significantly increased the abundance of beneficial bacteria, involving Lactobacillaceae and Bacteroidetes, and decreased the abundance of Ruminococcaceae, Prevotellaceae, and Burkholderiaceae. Overall, our results provided a basis for using the P. lobata extract as a promising and potential functional ingredient for the food industry.